PENGARUH PENGUNGKAPAN ENVIRONMENTAL, SOCIAL DAN GOVERNANCE (ESG) TERHADAP KINERJA PERUSAHAAN PADA PERUSAHAAN SUB SEKTOR PERTAMBANGAN BATU BARA PERIODE 2017-2022 - Durlista, Machillah Afany; Wahyudi, Ickhsanto (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2023)
This study aims to analyze and test the effect of Environmental, Social, and Governance (ESG) disclosures on company performance. Company performance in this study consists of operational performance (ROA), financial performance (ROE), and market performance (Tobin's Q). ESG disclosure standard guidelines use the Global Reporting Initiative (GRI). The population of this study were coal mining sub-sector companies listed on the IDX from 2017 to 2022. The sample selection used purposive sampling with 5 companies and used multiple linear regression data analysis. The results of this study indicate that environmental disclosure has a positive effect on operational performance and financial performance, but has no effect on market performance. Social disclosure has a positive effect on market performance, but does not affect operational performance and financial performance. While governance has a positive effect on financial performance and market performance, it has no effect on operational performance. The implication is that increasing awareness and compliance with corporate social responsibility towards the environment, social and governance of the impact of the company's operational activities is a way for the company's sustainability